PENGARUH ATRIBUT PRODUK DAN PERILAKU PENCARIAN VARIASI TERHADAP PERILAKU MAHASISWA BERPINDAH MEREK PONSEL PADA FAKULTAS EKONOMI DAN BISNIS ISLAM UINAM - Efendi, Ahmad; Jusmiati, Jusmiati (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2017)
The youth, especially student, is oftentimes categorized as a group consumer which tend to open to new product which peeped out [by] [in] marketing. This group [is] believed always follow life style trend nowadays. They even volunteer [release] money to buy new brand ponsel. This matter [is] [done/conducted] not merely for requirement but for the easiness of / desire of person. So that they will not loyal to a[n brand. This phenomenon [is] usually referred [as] [by] migratory behavior [of] brand. Target of research that is to the influence of product attributes and variation seeking behaviour toward students’ behavior of switching the brand of mobile phone in islamic economy and business faculty. This Research type [is] quantitative. Sampling in this research use method of stratified random sampling. Technique data collecting use disseminated kuesioner to Faculty Of Economics student and assumed Business Islam as according to [done/conducted] research counted 170 sampling.The data were analyzed using validation test, reliability test, classical assumption test, multiple linear regression test, correlation coefficient, coefficient of determination (R²), and hypothesis test using SPSS version 21.0 Result of research indicates that product attribute and of variety seeking behavior have an effect on to behavior of migratory student [of] brand either through simultan and also by parsial. As for dominant variable influence behavior of migratory student [of] brand that is variable of variety seeking behavior.